Applying Total Quality Management in Pedagogy - Goyal, Naresh Kumar (Journal of Commerce and Trade, 2008)
The developmental needs in education should be interpreted in the context of the overall developmental needs of the country and should take into consideration the developmental plans in other sectors. Education itself aims at development of human resources. Therefore when one talks of TQM in education it means development of those human resources which are involved in organizing, imparting and receiving education. Quality education denotes developing individuals comprehensively to their full potential, unfolding the perfection already existing in them. The challenge of management of quality in education is realizing optimally the perfection already prevailing in individuals, not only among students but also among teachers and all those who are some way or the other connected with imparting and organizing education.